Restorative Justice Paradigm As A Means In Solving Violent Crimes Against People or Goods - Pertiwi, Nyimas Maharani Putri; Dewi, Erna; Amrullah, Rinaldy (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine the restorative justice paradigm as a means of solving violent crimes against people or goods. Violent crime is an act prohibited by law by a person or group of people using physical force so as to cause physical damage to the victim, helplessness of the victim, damage to the victim's property / property, even lead to death. which is a repressive approach as implemented in the Criminal Justice System. The research method used is a normative research method, using a statute approach and case approach related to the restorative justice paradigm as a means of solving violent crimes against people or goods. The statute approach is to examine matters concerning legal principles, legal views and doctrines, and laws and regulations related to Criminal Acts of Violence Against Persons or Goods and can be held accountable for their truth while the case approach is an approach that is carried out to analyze, analyze and analyze used as a guideline for legal problems to resolve legal cases. This research uses secondary data supported by primary material and will be analyzed with analysis content.